1979
DOI: 10.1111/j.1526-4610.1979.hed1901008.x
|View full text |Cite
|
Sign up to set email alerts
|

Iris Adrenergic Impairment in Idiopathic Headache

Abstract: SYNOPSIS Adrenergic iris neurons were pharmacologically studied in 30 migraineurs, 11 cluster headaches and 30 controls. The pupillary diameter was measured by photographic technique. When compared with controls, migraineurs showed minor fenfluramine mydriasis and greater, more prolonged guanethidine miosis. No significant differences between the affected and unaffected side were observed by testing with guanethidine in unilateral migraineurs. A poor concentration and synthesis of noradrenaline in the pupil te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 15 publications
5
83
0
Order By: Relevance
“…Between successive attacks of migraine and during an attack, a smaller pupil diameter and a higher degree of anisocoria with smaller pupil size on the symptomatic side has been observed [4,8]. After local bilateral direct sympathetic activation by application of drugs such as cocaine and phenylephrine, pupillary dilatation was more pronounced in migraine sufferers than in controls [4,12,17], suggesting central sympathetic dysfunction [12]. Furthermore, following indirect activation of the sympathetic innervation, the pupillary dilatation was less marked compared with controls, suggesting a dysfunction of the tertiary sympathetic neuron [7].…”
Section: Introductionmentioning
confidence: 95%
“…Between successive attacks of migraine and during an attack, a smaller pupil diameter and a higher degree of anisocoria with smaller pupil size on the symptomatic side has been observed [4,8]. After local bilateral direct sympathetic activation by application of drugs such as cocaine and phenylephrine, pupillary dilatation was more pronounced in migraine sufferers than in controls [4,12,17], suggesting central sympathetic dysfunction [12]. Furthermore, following indirect activation of the sympathetic innervation, the pupillary dilatation was less marked compared with controls, suggesting a dysfunction of the tertiary sympathetic neuron [7].…”
Section: Introductionmentioning
confidence: 95%
“…However, he exhibited manifestations of transient sympathicoparesis, typical of acute attacks of cluster headache. [26][27][28][29] Recently, a patient was reported who, after 20 years of freedom from chronic cluster headache, had a relapse after a carotid thrombendarterectomy. It was concluded that the relapse might possibly be secondary to peroperative damage of the carotic sympathetic plexus.…”
Section: Clinical Features Of Sellar/suprasellar and Parasellar Pathomentioning
confidence: 99%
“…Tyramine eyedrops have been used successevoked mydriasis in healthy subjects. We used methoxamine-evoked mydriasis as a control: methoxamine is a fully in ophthalmic pharmacology as a diagnostic tool in Horner's syndrome [2 ] and in cluster headache directly acting a 1 -adrenoceptor agonist whose effect is not dependent on the size of the presynaptic noradrenaline patients [ 3,4]. In both clinical syndromes, indirectly acting sympathomimetic amines such as tyramine and store [17 ].…”
Section: Introductionmentioning
confidence: 99%
“…hydroxyamphetamine may have a reduced effectiveness in evoking mydriasis. The reduced effectiveness of the indirectly acting sympathomimetic amines is attributed to an impairment of the uptake and/or noradrenaline storage mechanisms in the terminals of the peripheral Methods sympathetic neurones innervating the dilator muscle of the iris [2,3,5]. Furthermore, in Horner's syndrome the Ethical considerations reduced effectiveness of tyramine is regarded as evidence for a postganglionic lesion.…”
Section: Introductionmentioning
confidence: 99%